Impact of a culturally adapted health belief model-based nutrition intervention on nutritional status among children under five in rural Indonesia - Elly Dwi Masita; Esteve Adrian Estiva; Annif Munjidah; Uke Maharani Dewi; Hinda Novianti (AcTion: Aceh Nutrition Journal, 2026)
Child malnutrition is a major public health concern in Indonesia. The 2024 Indonesian Nutritional Status Survey reported stunting, wasting, and overweight prevalence among children under five years of age at 19.8%, 7.4%, and 3.4%, respectively, indicating persistent nutritional challenges despite national improvements. This study aimed to assess the effectiveness and contextual implementation of a culturally adapted Health Belief Model–based nutrition intervention on child nutritional status in rural Indonesia. A quasi-experimental mixed-methods study with a one-group pre-test and post-test design was conducted among 179 caregiver–child dyads in rural East Java from January to April 2025 without a control group. The nutritional status of the children was assessed using weight-for-age, height-for-age, weight-for-height, and BMI-for-age z-scores. Quantitative data were analyzed using the Marginal Homogeneity Test, while qualitative data were analyzed thematically. The intervention was associated with a statistically significant shift in the distribution of nutritional status (χ²=114.94; df=4; p<0.001; Cramer’s V=0.40; 95% CI=0.32–0.47), indicating a moderate effect. Normal nutritional status increased from 12.3% to 70.9%, whereas underweight decreased from 50.3% to 6.7%. Qualitative findings indicated that cultural beliefs, family decision-making, food insecurity, and economic constraints influenced child-feeding practices. In conclusion, the intervention was associated with improved child nutritional outcomes and caregiver readiness; however, the findings should be interpreted cautiously, given the absence of a control group and the short intervention period.